Prevalence of high blood pressure and associated factors among adolescents and young people in Tanzania and Uganda. Issue 4 (27th February 2019) - Nsanya, Mussa K.; Kavishe, Bazil B.; Katende, David; Mosha, Neema; Hansen, Christian; Nsubuga, Rebecca N.; Munderi, Paula; Grosskurth, Heiner; Kapiga, Saidi
Abstract : We conducted a cross‐sectional study among school/college students in Tanzania and Uganda to determine the prevalence of high blood pressure (BP) and associated factors. Participants were classified to have high BP if they had pre‐hypertension or hypertension. Interviews were done using the WHO STEPS instrument. Using data from both countries (n = 1596), the overall prevalence of high BP was 40% (95% CI: 37‐42). The prevalence of pre‐hypertension was 29% (95% CI: 26‐31) and that of hypertension was 11% (95% CI: 10‐13). High BP was independently associated with obesity (aOR = 6.7, 95% CI: 2.2‐20.0), male sex (aOR = 3.2, 95% CI: 2.4‐4.4), and among males aged above 20 years (aOR = 5.5, 95% CI: 2.9−10.5). Consumption of fruits/vegetables was associated with decreased odds for high BP (aOR = 0.7, 95% CI: 0.50‐0.98). The increasing burden of pre‐hypertension across age groups could explain the early onset of hypertension and cardiovascular diseases (CVDs) among young African adults. There is a need for longitudinal studies to explore the drivers of pre‐hypertension in East African adolescents.